THE IMPACT OF TEACHERS' PROFESSIONAL DEFORMATION ON THE PROCESS OF SOCIALIZATION. (Universal International Scientific Journal, 2026)
This article scientifically analyzes the cases of professional deformation in teachers, the causes of their formation and their impact on the process of socialization. The impact of psychological changes, communication problems and stereotyped thinking patterns that occur during pedagogical activity on personal development is highlighted. According to the results of the study, it was found that professional deformation significantly affects the social relations, professional activity and personal development of the teacher. Also, pedagogical and psychological recommendations are provided to prevent these cases.
Keywords: professional deformation; pedagogical personality; socialization